Digitalization of education : opportunities and challenges for sustainable higher education and learning - Azizuddin, Mohammad; Shamsuzzoha, Ahm; Iqbal, Mohammad (Computers and Industrial Engineering, 2024)
This research paper aims to scholarly understand and take part in debates regarding the digitalization of education with sustainable higher education and learning. The invention and practice of digital facilities in higher education during and after the Covid-19 era have created ample opportunities as well as various challenges for higher education worldwide. Based on such circumstances, this study identified two research questions, namely: (i) What are the added opportunities digitalization of education offers to maintain sustainable education and learning, and (ii) What are the accompanying challenges behind the digitalization of education and how to address them? This paper is a qualitative study based on gleaned data from both primary and secondary sources. The findings implicate academics and university senior management to reassess the study curriculum and delivery, and adopt and offer dynamic academic programs of higher education, considering the impact of digitalization of education on sustainable higher education and learning. In this study, a research-enriched learning curriculum and effective delivery with an innovative pedagogical approach are also proposed.
Keywords: Active learning; Curriculum design; Digitalization; Innovative pedagogy; SDGs; Sustainable higher education; fi=Tuotantotalous|en=Industrial Management|